Characteristics and experiences of lactating women with measured low milk production - Theresia Margaretha Nicole Manshanden; Sarah Gallo Abelha; Joost Velzel; Jacki Louise McEachran; Donna Tracy Geddes; Sharon Lisa Perrella (International Breastfeeding Journal)
Abstract Objective This study aimed to compare the characteristics and experiences of women with measured low and normal 24 h milk production. Methods We analysed data from a nested case-control study of 136 participants who measured their 24 h milk production within 1–6 months of birth and completed an online survey of lactation risk factors and experiences within 2 years of birth. The study was conducted between January 2020 and March 2024. 24 h milk production, calculated as the sum of all pre-post breastfeed and expression weights, was classified as low (< 600 mL) or normal milk production (≥ 600 mL). The prevalence of anatomical, endocrine/metabolic, pregnancy, birth complications and postpartum lactation risk factors was reported. Further, the experiences of participants that reported low milk production were described. Results Low milk production was measured in 39 out of 136 participants (29%). Breast hypoplasia was more prevalent in this group (low milk production 13%; normal milk production 3%; p = 0.03). Of those with measured low milk production 21% perceived production was normal. In participants with measured normal production 28% had perceived low production. Formula use was more common among those with low milk production, and their infants had significantly lower weight-for-age z-scores despite similar birth weights. Qualitative data reflected the stress and effort expended in trying to increase milk production, and 10/26 (39%) rated lactation consultant support as most helpful in managing their milk production. Conclusions Low milk production is a multifactorial and common concern, affecting nearly one in three breastfeeding women. While some contributing risk factors such as breast hypoplasia were identified, over half of the affected participants had not received an explanation from their healthcare provider. This underscores that low milk production is not always fully explainable or treatable, and highlights the need for personalized supportand further research to improve clinical assessment and effective management.